Effect of fiber loading on properties of thermoplastic sago starch/kenaf core fiber biocomposites - Sarifuddin, Norshahida; Ismail, Hanafi; Ahmad, Zuraida (North Carolina State University * College of Natural Resources, 2012)
Growing attention has been paid to the innovation of ecological products, prompted by rising environmental concerns. As a natural polymer, thermoplastic sago starch has been regarded as an alternative material to petroleum-based plastic owing to its availability, cost, and biodegradability. In order to produce thermoplastic starch materials with enhanced structural and functional stability during use, kenaf fibers were incorporated as the reinforcing filler. In this work, thermoplastic sago starch (TPSS)/kenaf core fiber (KF) biocomposites were prepared at different fiber loadings (0 to 35 wt.%), and the effects of fiber loading were analyzed by mechanical tests, TGA, FTIR, SEM, and water absorption behavior. The tensile analysis showed a linear increase in strength and modulus upon increasing fiber content until it reached an optimum at 30 wt.% fiber loading. The thermal stability of biocomposites was improved slightly by the incorporation of kenaf fibers into TPSS matrices. FTIR results indicated a change in the functional group of the biocomposites. Moreover, the interfacial adhesion properties of biocomposites were evident from morphological studies of tensile fracture surfaces. It is interesting to note that water absorbed by the biocomposites was reduced by the addition of fiber, and it seems that the hydrophilic character was decreased especially for the glycerol-plasticized sample. The results obtained clearly illustrate the potential use of these fiber and biopolymers to establish their suitability as alternative biocomposite materials.